A result on total coloring of circulant graphs - Alves Junior, Mauro N.; Sasaki, Diana (Anais do Encontro de Teoria da Computação (ETC); 2020: Anais do V Encontro de Teoria da Computação, 2020)
In this work we determine that all members of an infinite family of 4-regular circulant graphs are Type 1.